الأوقاف الهبطية في ضوء تعقبات الشيخ الغماري "ربع ياسين أنموذجا - عمري, خولة (University of eloued جامعة الوادي, 2021)
"تناولت هذه الدراسة: ""الأوقاف الهبطية في ضوء تعقبات الشيخ الغماري -ربع ياسين أنموذجا-""، وتهدف إلى مدى صحة ذلك، من خلال إظهار الجوانب اللغوية والنحوية والتفسيرية التي كان لها أثر في الوقف الهبطية المبنية على اختيارات العلماء، حيث مهدت بالموضوع بمقدمة طرحت فيها أهمية وأسباب التي دفعتني لاختيار هذا الموضوع، بحيث جاء البحث في 4 مباحث وهي: -الأول: قمت بتعريف علم الوقف وكل ما يدور حوله. -ثانيا: عرفت بالإمام الهبطي، ذاكرة العومل التي دفعته لإختيار هاته الوقوف. -ثالثا: عرفت بالإمام الغماري، كما قمت بدراسة كتابه الذي جمع فيه بعض الأوقاف المتعسفة كما رأها هو. -رابعا: وفيه الدراسة التطبيقية لتلك التعقبات. وختمت دراستي بجملة من النتائج وتوصيات. "This study dealt with: “Landing Endowments in the Light of the Traces of Sheikh Al-Ghamari -Rab’ Yassin as a Model-”، and aims to verify the validity of this، by showing the linguistic، grammatical and explanatory aspects that had an impact on the descending endowments based on the choices of scholars، where it paved the subject with an introduction in which it was presented The importance and reasons that prompted me to choose this topic، as the research came in 4 topics، which are: - The first: I defined the science of waqf and everything that revolves around it. - Secondly: I was known as Imam al-Habti، the memory of the factors that prompted him to choose this stand. - Third: I got to know Imam Al-Ghamari، and I also studied his book in which he collected some arbitrary endowments as he saw them. - Fourth: It includes the applied study of those traces. I concluded my study with a set of results and recommendations. "
علوم قرآن
Keywords: الأوقاف الهبطية، الغماري، تعبات، ربع ياسين.; The Landing Endowments, Al-Ghamari, Tabat, Rab' Yassin.